Corporate Risk Management : Theory and Applications. - Dionne, Georges (John Wiley & Sons, Incorporated, 2019)
An updated review of the theories and applications of corporate risk management After the financial crisis of 2008, issues concerning corporate risk management arose that demand new levels of oversight. Corporate Risk Management is an important guide to the topic that puts the focus on the corporate finance dimension of risk management. The author--a noted expert on the topic--presents several theoretical models appropriate for various industries and empirically verifies theoretical propositions. The book also proposes statistical modeling that can evaluate the importance of different risks and their variations according to economic cycles. The book provides an analysis of default, liquidity, and operational risks as well as the failures of LTCM, ENRON, and financial institutions that occurred during the financial crisis. The author also explores Conditional Value at Risk (CVaR), which is central to the debate on the measurement of market risk under Basel III. This important book: Includes a comprehensive review of the aspects of corporate risk management Presents statistical modeling that addresses recent risk management issues Contains an analysis of risk management failures that lead to the 2008 financial crisis Offers a must-have resource from author Georges Dionne the former editor of The Journal of Risk and Insurance Corporate Risk Management provides a modern empirical analysis of corporate risk management across industries. It is designed for use by risk management professionals, academics, and graduate students.